2014
DOI: 10.1109/jphotov.2013.2292350
|View full text |Cite
|
Sign up to set email alerts
|

Current Conduction Mechanism of Front-Side Contact of N-Type Crystalline Si Solar Cells With Ag/Al Pastes

Abstract: Recently, n-type crystalline Si (c-Si) cells with frontside (FS) metallization Ag/Al paste have attracted considerable attention. However, a clear understanding of current conduction mechanism is still lacking. We report here the results of our microstructural investigation of the interfacial contact region using electron microscopy techniques. In optimally fired cells, we did not find any Al-Si eutectic layer on the emitter surface that would support a regrowth mechanism as found during the back surface field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…To summarize the discussion of the J 0e,met values, we found so far no striking evidence for an additional recombination path besides the metal/Si interface recombination. This is in agreement with recent findings from Liang et al that no Si–Al alloy formation was observed in structural investigations of Ag/Al screen‐printed contacts. The rather moderate J 0e,met values are reflected in the rather moderate V OC losses.…”
Section: Single Recombination Lossessupporting
confidence: 94%
“…To summarize the discussion of the J 0e,met values, we found so far no striking evidence for an additional recombination path besides the metal/Si interface recombination. This is in agreement with recent findings from Liang et al that no Si–Al alloy formation was observed in structural investigations of Ag/Al screen‐printed contacts. The rather moderate J 0e,met values are reflected in the rather moderate V OC losses.…”
Section: Single Recombination Lossessupporting
confidence: 94%
“…They assume a deep metal penetration into the silicon to simulate the increased surface recombination. On the other hand, Liang et al [13] recently reported that they found no evidence of aluminum diffusion from the Ag/Al paste into the silicon. The remaining hypothesis (ii) to (iv) are to be proven and further experiments on these hypothesis are ongoing.…”
Section: Discussion Of Enhanced Contact Recombinationmentioning
confidence: 96%
“…Different conduction models may also need to be considered. 25 For example, nanoAg colloids in the interfacial glass layer would also contribute to low contact resistivity. 12 But here we limit our studies in the fritless paste contacting with the boron-doped Si emitters.…”
Section: Aip Advances 7 015306 (2017)mentioning
confidence: 99%